Tie a bow, Ben Bunny : a lacing book with step-by-step instructions - Smith, Mavis (New York : Scholastic Inc, 1996)
Ben Bunny hopped along the street with brand new sneakers on his feet. "Nice shoes, Ben!" a little crow cried. "Too bad your laces are untied!"
Keywords: Lacing; Bunnies stories-Fiction